Predicting FIR lines from simulated galaxies. Issue 4 (26th June 2020) - Lupi, Alessandro; Pallottini, Andrea; Ferrara, Andrea; Bovino, Stefano; Carniani, Stefano; Vallini, Livia
ABSTRACT: Far-infrared (FIR) emission lines are a powerful tool to investigate the properties of the interstellar medium, especially in high-redshift galaxies, where ALMA observations have provided unprecedented information. Interpreting such data with state-of-the-art cosmological simulations post-processed with cloudy, has provided insights on the internal structure and gas dynamics of these systems. However, no detailed investigation of the consistency and uncertainties of this kind of analysis has been performed to date. Here, we compare different approaches to estimate FIR line emission from state-of-the-art cosmological simulations, either with cloudy or with on-the-fly non-equilibrium chemistry. We find that [C ii ]158μ predictions are robust to the model variations we explored. [O i ] emission lines, that typically trace colder and denser gas relative to [C ii ]158μ, are instead model dependent, as these lines are strongly affected by the thermodynamic state of the gas and non-equilibrium photoionization effects. For the same reasons, [O i ] lines represent an excellent tool to constrain emission models, hence future observations targeting these lines will be crucial.